A Case Study "Post" of Serbia: The Impact of Intranet Design on Efficient Functioning of E-Business - Borislav Kolaric; Robert Petrovic; Slobodan Radojcic (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
E-business is playing a larger and more important role in today’s modern business environment. In many firms, regardless of their activity or size, electronic communication has become an unavoidable part of business processes. This entails the development and extension of effective external electronic communication with customers, as well as the strengthening of internal electronic communication among employees. This study is an attempt to investigate the effectiveness of applying the intranet in the company "Post" of Serbia. Basis of the research were the employees in "Post" of Serbia, in the region of Srem. The purpose of this paper was to determine the relationship between intranet design and its efficient operation in the company Post of Serbia. According to research and analysis of the results obtained, the current intranet design does not provide its true application, weakening its very important function in terms of supporting the company’s e-business. The fact that Serbia is a country in transition, and that market liberalization has a large impact on the operation of public services, emphasises the importance of subject research.Scientific information obtained through research on the title subject may be useful in the management of public services in Serbia and other countries in transition.